2023
DOI: 10.3390/app13063496
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates and Their Influence on the Implant Failure: A Systematic Review

Abstract: Objective: The goal of this systematic review was to study the relationship between the use of bisphosphonates (oral or intravenous) and its effect on implant osseointegration. Methods: The focused question was “In patients medicated with bisphosphonates and who underwent surgery to place dental implants, what is the influence of that medication (of different generations) on the failure of dental implants (O)?” Following specific eligibility criteria, four databases (PubMed/MEDLINE, Scopus, Web of Science, DOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…It is common to find patients with osteoporosis taking medications, such as bisphosphonates. Within this aspect, Rebelo et al [28] demonstrated the influence of bisphosphonates on implant failure; the authors concluded a high mean failure rate of implant osseointegration (49.96%) was found to be associated…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common to find patients with osteoporosis taking medications, such as bisphosphonates. Within this aspect, Rebelo et al [28] demonstrated the influence of bisphosphonates on implant failure; the authors concluded a high mean failure rate of implant osseointegration (49.96%) was found to be associated…”
Section: Discussionmentioning
confidence: 99%
“…It is common to find patients with osteoporosis taking medications, such as bisphosphonates. Within this aspect, Rebelo et al [28] demonstrated the influence of bisphosphonates on implant failure; the authors concluded a high mean failure rate of implant osseointegration (49.96%) was found to be associated with the medication, regardless of the bisphosphonates' generation; therefore, the failure rate was lower in patients using second-generation bisphosphonates (Alendronate and Pamidronate) and higher with the IV administration compared to the oral administration. Then, strategies were studied in order to improve the development of functional biomaterials for delivering multiple growth factors, which are effective strategies for bone repair in a temporally controllable carrier and, thus, improve the therapeutic effect [29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the failure rate was higher with IV administration of bisphosphonates compared to oral administration, and it was lower in patients utilizing secondgeneration bisphosphonates (alendronate and pamidronate). 175 There are controversies regarding discontinuing bisphosphonate therapy before and/or after dental implant surgery. In a study by Tripodakis et al, 176 a 3-month drug holiday (second-and thirdgeneration bisphosphonates; alendronate and risedronate) before and after implant placement + postoperative antibiotic therapy resulted in a successful implant treatment during a 2-year follow-up.…”
Section: Medication-related Osteonecrosis Of the Jawsmentioning
confidence: 99%
“…[47]. Both early and late implant failure may be affected by patient characteristics (i.e., non-modifiable risk factors such as age, sex, immune status, chronic conditions or diseases, oral status and inadequate oral hygiene, periodontal disease, bruxism, medication intake, smoking) and adherence to treatment guidelines [48]. Pre-surgical implant planning and bone preparation are some of the critical aspects to ensure a successful intervention and a pleasing outcome of implant-supported prostheses.…”
Section: Implant Loading -Undisturbed Healing Period For Osseintegrationmentioning
confidence: 99%
“…Implant bed preparation should be performed as effectively and gently as possible, to ensure the primary healing and the long-term success of the implants [48]. The conventional drilling is a commoly used technique to prepare implant nests [49]; first, a gradual drilling of the osteotomy site occurs, which is later enlarged to the desired diameter.…”
Section: Implant Loading -Undisturbed Healing Period For Osseintegrationmentioning
confidence: 99%